The Fourth Amendment : original understandings and modern policing - Mannheimer, Michael J. Z. (University of Michigan Press, 2023)
Police are required to obey the law. While that seems obvious, courts have lost track of that requirement due to misinterpreting the two constitutional provisions governing police conduct: the Fourth and Fourteenth Amendments. The Fourth Amendment forbids "unreasonable searches and seizures" and is the source of most constitutional constraints on policing. Although that provision technically applies only to the federal government, the Fourteenth Amendment, ratified in the wake of the Civil War, has been deemed to apply the Fourth Amendment to the States. This book contends that the courts' misinterpretation of these provisions has led them to hold federal and state law enforcement mistakenly to the same constitutional standards. The Fourth Amendment was originally understood as a federalism, or "states' rights," provision that, in effect, required federal agents to adhere to state law when searching or seizing. Thus, applying the same constraint to the States is impossible. Instead, the Fourteenth Amendment was originally understood in part as requiring that state officials (1) adhere to state law, (2) not discriminate, and (3) not be granted excessive discretion by legislators. These principles should guide judicial review of modern policing. Instead, constitutional constraints on policing are too strict and too forgiving at the same time. In this book, Michael J.Z. Mannheimer calls for a reimagination of what modern policing could look like based on the original understandings of the Fourth and Fourteenth Amendments.
Keywords: United States. -- Constitution. -- 4th Amendment.; United States. -- Constitution. -- 14th Amendment.; Constitution (United States); Police -- Law and legislation -- United States.; Searches and seizures -- United States.; Police.; Searches and seizures.; United States.